Reflexão sobre o trabalho, vivências e práticas musicais de mulheres compositoras em Manaus a partir de 2000 - Guimarães, Klissy Kely (2020)
This study intends to reflect interdisciplinarily the question of music as an instrument of work, resistance, identity and empowerment of composers working in Manaus from the years 2000 to 2019. The reasons for this time frame are based on three factors distributed in the respective plans social: First, due to the greater investigation and implementation of women's rights in the country, legal. Second, greater purchasing power for Brazilians in general, which had an impact on the production and visibility of the work of the composers in question, due to the reduction of bureaucracy in this process since the 2000s, an economic one. Third, through the transition from the way of making, producing and listening to (consuming) music from analog to digital, of technological innovation. The means and analyzes of the materials collected in newspapers, magazines, collections and interviews recorded in audio and video carried out during this research will be presented, in order to provide means for a critical reflection about the life and musical field of Manaus, where they work said composers. The use of Critical Discourse Analysis - ADC will provide theoretical support for a way of thinking about the content of ten lyrics of songs composed by some of them in that timespace, presenting how they dialogue, influence, interfere and relate to their social environment . Starting from a historical musicological premise also with regard to the discussion of various cultures that immigrated to the city that somehow wove the cultural manifestations produced in it, resulting in the phenomena of “glocalization” and also in cultural syncretism. We will discuss the role of local media, the State, public policies, festivals and musical exhibitions as legitimizers of the work of composers in Manaus within the aforementioned period. However, it is essential to debate how the main theories of social, legal and scientific knowledge prevalent in the last two centuries have exercised power over women as a whole, specifically in this city. Scrutinizing a description with an ethnographic pretension, how such conceptions, despite so many social transformations that the planet has been going through, reach contemporary music. It aims to understand the current social dynamics from historical fragments from an interdisciplinary perspective of criticism of colonialism. Historiographic reflections on social factors that may have contributed to the phenomenon of the invisibility of women as authors and consequently composers will also be presented. Finally, the annexes and appendices also include: a list with the names of composers, who were contacted in some way, either in bibliography or in person due to this research, in addition to compositions and poems composed by this author, stimulated by the subjects studied in this investigation.